Comparison of the Effects of Different Low Molecular Weight Heparins on the Hemostatic System Activation In Vivo in Man - Wolzt, Michael; Eder, Michaela; Weltermann, Ansgar; Entlicher, Jesusa; Eichler, Hans-Georg; Kyrle, Paul A (Thrombosis and Haemostasis, 1997)
In a double-blind, randomized, cross-over study the effects of single subcutaneous doses of 120 anti-Xa units/kg body wt. of three different low molecular weight heparin (LMWH) preparations were investigated in 15 healthy subjects by determination of thrombin-antithrombin El complex (TAT), prothrombin fragment 1.2 (fl.2), and β-thromboglobin (β-TG) in shed blood and in venous blood.Certoparin, dalteparin, and enoxaparin significantly inhibited coagulation activation marker formation in shed blood. The substantial inhibition of TAT and fl.2 formation was slightly more pronounced in response to certoparin. β-TG was decreased following certoparin and enoxaparin, but not following dalteparin. However, no difference between groups was detectable. A small but consistent decrease of fl.2 formation in venous blood was noted for all LMWHs and dalteparin and enoxaparin, but not certoparin, inhibited TAT formation. Only a minor impact of the three LMWH preparations was noted on β-TG plasma concentrations.Our data indicate that the studied LMWH preparations have a major impact on blood clotting in the activated state and inhibit in vivothe hemostatic system to a comparable extent.